PENERAPAN LAYANAN INFORMASI BIDANG BIMBINGAN PRIBADI SOSIAL DALAM MEMBENTUK AKHLAKUL KARIMAH DI SD NEGERI 81 MUARO JAMBI - Nasution, Nur Cahaya; Santera, Teri; Lubis, Putri Virani (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2024)
Abstract This research aims to determine the indicators of akhlakul karimah in students, methods of personal social guidance in forming akhlakul karimah and also obstacles in forming akhlakul karimah through personal social guidance in students at SD Negeri 81 Muaro Jambi. The method used in this research is a qualitative method with a descriptive approach. This type of research is field research with the research location at SD Negeri 81 Muaro Jambi. The subjects in this research were guidance and counseling teachers and 10 6th grade elementary school students, who were determined using purposive sampling techniques. The data collection techniques used were observation, interviews and documentation. Meanwhile, the data was analyzed by means of data reduction, data presentation, and drawing conclusions. The results of the research show that several indicators of akhlakul karimah in students at SD Negeri 81 Muaro Jambi include the implementation of worship, good manners, honesty, patience, gratitude, and tawadhu' (humility). The personal social guidance method in forming morals in students at SD Negeri 81 Muaro Jambi is a direct method carried out through individual methods and group methods. Meanwhile, obstacles in the formation of akhlakul karimah originate from internal factors, namely from individuals (students themselves) who are not yet serious about implementing these akhlakul karimah.Keywords: Personal Social Guidance; Akhlakul Karimah.